2022
DOI: 10.3390/molecules27061966
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypyridinone-Based Metal Chelators towards Ecotoxicity: Remediation and Biological Mechanisms

Abstract: Hydroxypyridinones (HPs) are recognized as excellent chemical tools for engineering a diversity of metal chelating agents, with high affinity for hard metal ions, exhibiting a broad range of activities and applications, namely in medical, biological and environmental contexts. They are easily made and functionalizable towards the tuning of their pharmacokinetic properties or the improving of their metal complex thermodynamic stabilities. In this review, an analysis of the recently published works on hydroxypyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…The design and preparation of compound 16 was done in isomerically pure form. A panel of probes was prepared where the Phe-residue in the tetrapeptide sequence central part (18,(21)(22), at the nitrogen-terminus (19) or the carbon-terminal lysine (20) was replaced by the dual fluorescent probe. A structural analog of 20 was represented by compound 23, where a protected Fechelating moiety (17) was incorporated into the structure.…”
Section: Sensing Of Iron In Living Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and preparation of compound 16 was done in isomerically pure form. A panel of probes was prepared where the Phe-residue in the tetrapeptide sequence central part (18,(21)(22), at the nitrogen-terminus (19) or the carbon-terminal lysine (20) was replaced by the dual fluorescent probe. A structural analog of 20 was represented by compound 23, where a protected Fechelating moiety (17) was incorporated into the structure.…”
Section: Sensing Of Iron In Living Systemsmentioning
confidence: 99%
“…The latest review on hydroxypyridinone was reported in 2022. 22 Most reviews focused on the therapeutical applications of HOPOs and other aspects. A review completely dedicated to the sensing properties has not been compiled despite the availability of several papers on the sensing aspect.…”
Section: Minati Baralmentioning
confidence: 99%
“…Hydroxypyridinones have extensive applications in drug discovery for their unique ability to coordinate metal ions. A carboxylic acid-modified 3-hydroxy-4-pyridone metal-binding pharmacophore (MBP) is present in FDA-approved antiviral drugs: dolutegravir ( 11 ), an HIV-1 INST inhibitor bearing a 5-carboxylate, and baloxavir ( 12 ), an influenza virus polymerase acidic (PA) endonuclease inhibitor containing a 2-carboxylate (Figure A). In addition, an extensive series of potent influenza virus PA endonuclease inhibitors exemplified by 13 features the HPCA metal chelating triad with a 5-carboxylic acid (Figure A) .…”
Section: Metal-binding Inhibitor Types Of Pul89-cmentioning
confidence: 99%
“…3-Hydroxy-4-pyridones (3, are well-known bidentate chelation agents for many metals [1][2][3]. The first marketed drug possessing a 3,4-HPO scaffold, deferiprone (Ferriprox), is an iron chelating agent for treating thalassemia approved in 1999 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The first marketed drug possessing a 3,4-HPO scaffold, deferiprone (Ferriprox), is an iron chelating agent for treating thalassemia approved in 1999 (Figure 1). Since the pyridine ring offers great possibilities for functionalization, a number of new 3,4-HPO-based polydentate chelators [2,4] and also 3,4-HPO-grafted fabrics for filtering uranium from wastewater [5] were developed afterward. Moreover, there are some natural examples of 3,4-HPOs, such as rubrifacine [6] and mimosine (leucenol), an amitotic agent first isolated from Mimosa pudica [7].…”
Section: Introductionmentioning
confidence: 99%